Sediment prokaryotic assembly, methane cycling, and ammonia oxidation potentials in response to increasing antibiotic pollution at shrimp aquafarm - Xing, Guorui; Lu, Jiaqi; Xuan, Lixia; Chen, Jiong; Xiong, Jinbo (Journal of hazardous materials, 2022)
Antibiotic pollution poses serious threats to public health and ecological processes. However, systematic research regarding the interactive effects of increasing nutrient and antibiotic pollutions on the prokaryotic community, particularly taxa that contribute to greenhouse gas emissions, is lacking. By exploring the complex interactions that occur between interkingdom bacteria and archaea, biotic and abiotic factors, the responses of sediment prokaryotic assembly were determined along a significant antibiotic pollution gradient. Bacterial and archaeal communities were primarily governed by sediment antibiotic pollution, ammonia, phosphate, and redox potential, which further affected enzyme activities. The two communities nonlinearly responded to increasing antibiotic pollution, with significant tipping points of 3.906 and 0.979 mg/kg antibiotics, respectively. The combined antibiotic concentration-discriminatory taxa of bacteria and archaea accurately (98.0% accuracy) diagnosed in situ antibiotic concentrations. Co-abundance analysis revealed that the methanogens, methanotrophs, sulfate-reducing bacteria, and novel players synergistically contributed to methane cycling. Antibiotic pollution caused the dominant role of ammonia-oxidizing archaea in ammonia oxidation at these alkaline sediments. Collectively, the significant tipping points and bio-indicators afford indexes for regime shift and quantitative diagnosis of antibiotic pollution, respectively. Antibiotic pollution could expedite methane cycling and mitigate nitrous oxide yield, which are previously unrecognized ecological effects. These findings provide new insights into the interactive biological and ecological consequences of increasing nutrient and antibiotic pollutions. [Display omitted] •Bacterial and archaeal communities non-linearly responded to antibiotic pollution, with significant tipping points.•Antibiotic concentration-discriminatory taxa quantitatively diagnose in situ antibiotic concentrations.•Methanogens, methanotrophs, sulfate-reducing bacteria and novel players synergistically contributed CH4 cycling.•Antibiotic pollution caused AOA dominated ammonia oxidation, thus mitigate N2O yield.